Multiple synchronous rhabdomyomas in the tongue and floor of the mouth: case report - Sweed Ahmed Hassan; Bolzoni Alessandro; Anna Beltramini Giada; Baj Alessandro (EDP Sciences, 2019)
Observation: A 61-year-old male patient presented with tongue and base floor of the mouth firm swelling with intact overlying mucosa with ballottement by bimanual palpation. Histopathological examination and immunodiagnosis revealed this mass as adult rhabdomyoma. Comments: Any tongue base or floor of the mouth mass with intact overlying mucosa should be approached by magnetic resonance imaging with great concern of rhabdomyoma.